2012
DOI: 10.1128/jvi.00504-12
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of the Function of Glycoprotein H of Human Herpesvirus 6 Variant A by Glycoprotein H of Variant B in the Virus Life Cycle

Abstract: dHuman herpesvirus 6 (HHV-6) is a T-cell-tropic betaherpesvirus. HHV-6 can be classified into two variants, HHV-6 variant A (HHV-6A) and HHV-6B, based on genetic, antigenic, and cell tropisms, although the homology of their entire genomic sequences is nearly 90%. The HHV-6A glycoprotein complex gH/gL/gQ1/gQ2 is a viral ligand that binds to the cellular receptor human CD46. Because gH has 94.3% amino acid identity between the variants, here we examined whether gH from one variant could complement its loss in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Cell-free virus stocks were generated by concentrating the supernatant of highly infected JJHan cells and titrated by analysing the genome copies in newly infected cells by qPCR. Multi-step growth kinetics (Oyaizu et al, 2012;Nukui et al, 2015) revealed that the DU94 mutant had a significant growth defect compared to the wt and revertant virus (Fig. 1c), suggesting that the impaired HHV-6A replication is either due to the abrogation of U94 expression or effects on neighbouring genes such as U95 caused by deletion of the U94 sequences.…”
mentioning
confidence: 99%
“…Cell-free virus stocks were generated by concentrating the supernatant of highly infected JJHan cells and titrated by analysing the genome copies in newly infected cells by qPCR. Multi-step growth kinetics (Oyaizu et al, 2012;Nukui et al, 2015) revealed that the DU94 mutant had a significant growth defect compared to the wt and revertant virus (Fig. 1c), suggesting that the impaired HHV-6A replication is either due to the abrogation of U94 expression or effects on neighbouring genes such as U95 caused by deletion of the U94 sequences.…”
mentioning
confidence: 99%
“…6B). As mentioned previously, the HHV-6B gH/gL/ gQ1/gQ2 complex did not bind to CD46 (12), even when HHV-6B gQ1 formed a complex with HHV-6A gH, gL, and gQ2 (19) (Fig. 6C).…”
Section: Fig 3 Soluble Cd134 Blocks Hhv-6b Infection Soluble Cd134 Pmentioning
confidence: 71%
“…Human CD46 was identified as the cell receptor for HHV-6 (8) and binds the HHV-6A gH/gL/gQ1/gQ2 complex (9,10). Interestingly, we found that a similar glycoprotein complex exists in HHV-6B but does not bind to CD46 (11,12), even though it shares a relatively high sequence identity with the glycoprotein in HHV-6A (especially the gH and gL components). Recently, we found that human CD134 is a specific cellular receptor for HHV-6B and binds to the HHV-6B gH/gL/gQ1/gQ2 complex (13).…”
mentioning
confidence: 71%
“…These studies have almost exclusively focused on HHV-6A, as it is the only roseolovirus genome that has been cloned into a bacterial artificial chromosome (BAC) (11) and is therefore applicable to genetic manipulation. Examples of reverse genetic approaches in roseoloviruses include defining the role of viral glycoproteins in replication (11), and confirming the role of homologous genes conserved across the herpesvirus family (12). …”
Section: Functional Genomicsmentioning
confidence: 99%